Egrang as a Balance Training Tool Newtonian Modeling and Biomechanical Insights - Rafael Hagai (INDO PUBLISHING, 2025)
The balance game from Indonesia, Egrang, has been noted for its increasingly recognized cultural value, as well as for its physical challenge nature. This challenge, although it appears simple, comes from maintaining overall dynamic equilibrium — most importantly, control of the center of mass (CoM) and the base of support (BoS) during locomotion. In this case, Python simulations (which were done with the help of ChatGPT) within a Newtonian dynamic framework revealed two equilibrium stages within parameter-space: a static phase which is perpetually defined by symmetrical body weight distribution, and a dynamical phase which requires some bodily motion “lever” action to achieve rhythmic stepping. We performed a simulation and observed that it is a function of the step frequency, height of the stilts, and where the center of gravity is during the process. The challenge lies in maintaining dynamic control of the stances and the successful learning of this control process demonstrates the multitude of motor control mechanisms that are required for effective postural adaptation to stilts. These findings, confirmed by experiments, and others suggest that stilts could be used as an effective balance training tool.